Bystander editing by adenine base editors impairs vision restoration in a mouse model of Leber congenital amaurosis - Seok-Hoon Lee; Jun Wu; Dongjoon Im; Gue-ho Hwang; You Kyeong Jeong; Hui Jiang; Seok Jae Lee; Dong Hyun Jo; William A. Goddard, III; Jeong Hun Kim; Sangsu Bae (Molecular Therapy: Methods & Clinical Development)
Base editors (BEs) have emerged as a powerful tool for gene correction with high activity. However, bystander base editing, a byproduct of BEs, presents challenges for precise editing. Here, we investigated the effects of bystander edits on phenotypic restoration in the context of Leber congenital amaurosis (LCA), a hereditary retinal disorder, as a therapeutic model. We observed that in retinal degeneration 12 (rd12) of LCA model mice, the highest editing activity version of an adenine base editors (ABEs), ABE8e, generated substantial bystander editing, resulting in missense mutations despite RPE65 expression, preventing restoration of visual function. Through AlphaFold-based mutational scanning and molecular dynamics simulations, we identified that the ABE8e-driven L43P mutation disrupts RPE65 structure and function. Our findings underscore the need for more stringent requirements in developing precise BEs for future clinical applications.